THE DISCOURSE AS A WAY OF FORMING THE SOCIAL REALITY - Додонова, В. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the problem of alignment of discourse essence in linguistic and extralinguistic methodologies. The author analyses different approaches of modern Ukrainian and Western philosophers.